2008
DOI: 10.1038/sj.bjc.6604756
|View full text |Cite
|
Sign up to set email alerts
|

High density of FOXP3-positive T cells infiltrating colorectal cancers with microsatellite instability

Abstract: High-level microsatellite instability (MSI-H) in colorectal cancer accounts for about 12% of colorectal cancers and is typically associated with a dense infiltration with cytotoxic CD8-positive lymphocytes. The role of regulatory T cells that may interfere with the host's antitumoural immune response in MSI-H colorectal cancers has not been analysed yet. Using an antibody directed against the regulatory T-cell marker transcription factor forkhead box P3 (FOXP3), regulatory T cells were examined in 70 colorecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
80
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 37 publications
8
80
2
2
Order By: Relevance
“…In contrast, Michel et al [92] were the first to show that the density of FOXP3 + Treg cells infiltrating CRC were significantly higher in MSI-H tumors using immunohistochemistry, paralleling the enhanced number of CD8 + cells in these tumors. In addition, Sinicrope et al [96] showed that the intraepithelial to stromal ratios for FOXP3 + and CD3 + T cells were increased in MMR-deficient versus MMR-proficient colon cancers, yet the CD3 + /FOXP3 + ratio were similar in both groups and the prognostic impact of this ratio was maintained in the full study cohort.…”
Section: Foxp3 + Tregs Prognosis and Msi-statusmentioning
confidence: 91%
“…In contrast, Michel et al [92] were the first to show that the density of FOXP3 + Treg cells infiltrating CRC were significantly higher in MSI-H tumors using immunohistochemistry, paralleling the enhanced number of CD8 + cells in these tumors. In addition, Sinicrope et al [96] showed that the intraepithelial to stromal ratios for FOXP3 + and CD3 + T cells were increased in MMR-deficient versus MMR-proficient colon cancers, yet the CD3 + /FOXP3 + ratio were similar in both groups and the prognostic impact of this ratio was maintained in the full study cohort.…”
Section: Foxp3 + Tregs Prognosis and Msi-statusmentioning
confidence: 91%
“…The impact of lymphoid islets with germinal center-like architecture found in the vicinity of the tumors is debated and will be discussed below. Most authors considered the immune infiltrate as reflecting tumor cell modifications such as MSI (Popat et al, 2005;Le Gouvello et al, 2008;Michel et al, 2008), altered expression of major histocompatibility complex class I molecules (Bicknell et al, 1996) or production of chemokines (Balkwill, 2004) rather than representing a phenomenon that may control tumor dissemination. Immune infiltration was thus considered as an additional, rather weak, prognostic factor with no major impact on classical tumor, associated features, such as size (T), lymph node (N) or metastatic (M) invasion, oncogene mutation or VEGF production.…”
Section: Coordinated Adaptive Immune Response As the Strongest Prognomentioning
confidence: 99%
“…Indeed, multivariate analysis showed that the only significant prognostic factors related to locoregional control were T stage and T reg infiltration of the tumor (Badoual et al, 2006). In colorectal cancer, high densities of FoxP3 T cells were associated with MSI (Le Gouvello et al, 2008;Michel et al, 2008), a feature usually associated with favorable prognosis. We found no association between FoxP3, CTLA-4, GITR, IL-10, TGF-b and the presence of intratumoral or distant metastasis.…”
Section: T Regulatory Cells and Prognosismentioning
confidence: 99%
“…Further support for this argument comes from the fact that when T-regulatory cells were assessed by staining for the transcription factor, forkhead box P3 (FOXP3), this subtype of CD4? T cells was significantly increased in MSI tumors [19]. These findings underscore the importance of identification of individual subtypes of CD4?…”
mentioning
confidence: 58%
“…T cells, CD4? T-cell populations consist of several subtypes, such as T helper type 1 (Th1), Th2, Th17 and other T-regulatory cells [19]. In view of this, for future studies it may be worth expanding the scope of IHC staining to include markers that represent these specific T-cell subtypes.…”
mentioning
confidence: 99%